Microfinance Credit Accessibility and Financial Performance of Small and Medium Enterprises in Machakos County, Kenya - Muema Joseph Munguti; Lucy Wamugo (Integrated Journal of Business and Economics (IJBE), 2020)
SMEs in Machakos County have been characterized by poor financial performance which has been linked to financial access. Financial access is one of the keys that drive the development of SME in the country, particularly access to bank financing since banking sector plays a key role in serving this segment. This study specifically sought to determine the influence of collateral security, loan-income ratio and geographical branch penetration on financial performance of SMEs. Study adopted census survey due to small population size. Respondents were supplied with semi-structured questionnaires with aim of getting their views regarding financial accessibility and SME performance. Findings of the study indicated that collateral security, loan-income ratio, and geographical branch penetration has a significant positive effect on financial performance in Machakos County, Kenya. This research recommends that SME’s should improve their core capital, strengthen their financial management practices, foster financial innovation, and literacy within firms.